Pengaruh Persistensi Laba, Profit Potensial, Struktur Modal, dan Kesempatan Bertumbuh Terhadap Kualitas Laba - Lubis, Annisa Fitri; Sari, Shinta Permata (Jurnal EMT KITA, 2024)
Earnings quality is the precision of earnings information reflecting the company's actual performance and its reliability in predicting future performance as presented in financial statements. This study aims to analyze the impact of earnings persistence, potential profit, capital structure, and growth opportunities on earnings quality in industrial sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling technique used is purposive sampling, resulting in 107 firm-years that met the criteria as observation units. The data were analyzed using multiple linear regression analysis. The study's findings provide empirical evidence that potential profit and growth opportunities significantly influence earnings quality. However, earnings persistence and capital structure do not affect earnings quality.